Komunikasi Simbolik dalam Pengobatan Alternatif: Interpretasi Ritual Belian oleh Tokoh Adat Suku Dayak Basap: Penelitian - Rio Rahim; Eli Jamilah Mihardja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study explores symbolic communication in the Belian ritual as a form of alternative healing practiced by the Dayak Basap community in Keraitan Village, Kutai Timur Regency. The Belian ritual is regarded not merely as a healing practice but also as a medium of spiritual communication that connects humans with their ancestors and supernatural forces. The purpose of this study is to describe the process of symbolic communication within the Belian ritual and to interpret the meanings of symbols conveyed by customary leaders, particularly the Kepala Belian (chief shaman). The research employed a descriptive qualitative method with an ethnography of communication approach. Data were collected through participant observation and in-depth interviews with customary leaders and Belian shamans, and were analyzed using Dell Hymes’ SPEAKING model. The findings reveal that symbolic communication in the Belian ritual is manifested through chants, dances encircling the sriding, the sounds of gongs and drums, offerings, and wooden effigies that represent the patient. These symbols serve as a medium of interaction between humans, ancestors, and spirits believed to be the causes of illness. The Belian ritual functions not only as a traditional medical practice but also as a means of reinforcing cultural identity, fostering social solidarity, and preserving ancestral values.